Deuterium retention in deposited W layer exposed to EAST deuterium plasma - K. Katayama; N. Ashikawa; F. Ding; H. Mao; H.S. Zhou; G.N. Luo; J. Wu; M. Noguchi; S. Fukada (Nuclear Materials and Energy, 2017)
The deposited W layers formed on the W plate by hydrogen plasma sputtering were exposed to deuterium plasma in EAST together with bare W plate. In TDS measurement, the deuterium release was clearly observed from the deposited W layer in addition to the release of hydrogen which was incorporated during the sputtering-deposition processes. On the other hand, the release of hydrogen isotope was not detected from the bare W plate. This suggests that the formation of deposited W layers increases tritium inventory in the plasma confinement vessel. Although the thermocouple contacting to the backside of the W plate did not indicate a remarkable temperature rise, deuterium release peaks from the W layer were close to that from the W layer irradiated by 2keV D2+ at 573K. It was found by glow discharge optical emission spectrometry analysis that retained deuterium in the W layer has a peak at the depth of 50nm and gradually decreases toward the W substrate. From X-ray photoelectron spectroscopy analysis, it was evaluated that W oxide existed just at the surface and W atoms in the bulk of deposited W layer were not oxidized. These data suggest that hydrogen isotopes are not retained in W oxide but grain boundaries. Keywords: Deuterium retention, Deposited tungsten, EAST